Ice giant seismology: prospecting for normal modes. (25th December 2020) - Friedson, A. James
Abstract : The properties of ice giant normal mode oscillations, including their periods, spatial structure, stratospheric amplitudes and relative influence on the external gravity field, are surveyed for the purpose of formulating the best strategy for their eventual detection. Measurement requirements for detecting a normal mode's periodic pressure and temperature variations, including a possible stratospheric signal, and its effect on the external gravity field, are discussed in terms of its radial velocity amplitude at the 1 bar pressure level. It is found that for reasonable amplitudes, detection of the pressure and temperature variations of ice giant normal modes presents an extraordinary technical challenge. The prospects for detecting their gravitational influence on an orbiting spacecraft are more promising, with requirements that lie within the range of current technology. This article is part of a discussion meeting issue 'Future exploration of ice giant systems'.